A Study on Late Intake Valve Closing Miller Cycled Diesel Engine - Gonca, Guven; Sahin, Bahri; Ust, Yasin; Parlak, Adnan (SPRINGER HEIDELBERG, 2013)
NO (x) emissions released from diesel engines have much detrimental effects on the environment. Hence, these emissions must be decreased to the limited values described by regulations. One of the effective methods is to adopt Miller cycle to diesel engine in order to improve the performance and to reduce NO (x) emissions of a diesel engine. In this study, late inlet valve closing Miller cycle is applied to diesel engine by lowering compression ratio with respect to expansion ratio by closing intake valve 10 and 20 crank angles later than that of standard diesel engine by using zero-dimensional single zone model which was verified with experimental data. The obtained results have been compared with standard diesel engine in terms of performance and NO emissions. The results showed that Miller cycled diesel engine is found more efficient and environmentally friendly with less power output than standard diesel engine.
Keywords: Miller cycle; Diesel engine; Engine performance; NOx emission; PERFORMANCE ANALYSIS; HEAT-ENGINE; EMISSION; Science & Technology - Other Topics